The scientific management of deep carious lesions in vital teeth using contemporary materials—a narrative review - Al-Ali, M.; Camilleri, J. (Frontiers in Dental Medicine, 2022)
Aim The aim of this article is to review the scientific evidence for deep caries removal in permanent vital teeth and the choice of dentine replacement material and restoration of the teeth to maintain long-term tooth vitality and function. Method The two position statements, namely, the European Society of Endodontology and the American Association of Endodontists position statements on vital pulp therapy, will be scrutinized and compared with regard to the deep caries removal strategy and assessed for evidence of best practice. The properties of materials used to manage vital pulps and the best way to restore the teeth will be reviewed and guidance on the full management of vital teeth will be suggested. Conclusions Promoting new treatment modalities for reversible and irreversible pulpitis allowing for pulp preservation should be considered. Although debatable, cases with deep caries should be managed by complete non-selective caries removal which will allow for pulpal management if needed and a more predictable outcome can be expected when using the new materials and treatment modalities of vital pulp therapy.